Polyimide aerogels crosslinked through cyclic ladder‐like and cage polyamine functionalized polysilsesquioxanes. Issue 37 (31st May 2017) - Wu, Yi‐Wei; Ye, Miao‐Fen; Zhang, Wen‐Chao; Yang, Rong‐Jie
ABSTRACT: Polyimide (PI) aerogels with high porosity, low thermal conductivity, flexibility, low density, and excellent mechanical properties have attracted attention. However, the effect of crosslinker on structures and properties has not been investigated. Preparation of non‐shrinkable, aerogels with excellent performance is still a challenge. A series of PI aerogels are prepared through the polyamic acid oligomer reacting with different crosslinking agents: 1, 3, 5‐triaminophenoxybenzene (TAB), caged octa(aminophenyl) silsesquioxane, and cyclic ladder‐like poly(aminophenyl) silsesquioxanes. The shrinkage, density, porosity, and compression measurements of the PI aerogels indicate that the PI–polyhedral oligomeric silsesquioxanes (POSS) aerogels show more stable and stronger structures than with the TAB. The physical properties reveal that the introduction of POSS brings more compact and stable crosslinking network structures. The thermal properties of the PI aerogels are tested by dynamic mechanical analysis, thermal gravimetric analysis, and Transient Hot Wire method. The PI–POSS aerogels showed much better thermal stability, lower thermal conductivities, and better thermal insulation. Stable inorganic cores and rigid molecular structures of POSS result in strong mechanical properties, high thermal stability, and low thermal conductivities of the PI aerogels which may have important application in thermal protection against high temperature. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45296. Abstract :